Analisis Dampak Faktor-Faktor yang Mempengaruhi Pengangguran Terbuka di Kota Bogor - Anggraini Susanti; Desri Yohanna; Agryani Petra Sitorus; Syavira Nayla Shaumy; Muhammad Daniyal Stis; Nurlela Nurlela; Disya Ayu (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
Unemployment is an economic problem that can cause many negative symptoms, such as social symptoms that have an impact on violence within the household and outside the household itself. This is because the unemployed do not have income or income that can meet their daily needs. Therefore, research is needed as a solution to the problem of unemployment by measuring the level of influence of independent variables in the form of investment, wages, economic growth and inflation. The results of this research show that 78% of the independent variables have an influence on the dependent variable in the form of open unemployment in Bogor City for the 2013-2022 period. There are 22% remaining which are other factors not present in this study.